Nutrition Intervention in reducing gestational Diabetes Mellitus - Girma Mengistu, Assaye; Tarawally, Abubakar; Apriana Berkanis, Adelbertha; Indriani, Diah (PT. Publikasiku Academic Solution, 2024)
To review literature about Nutrition Intervention in reducing Gestational Diabetes Mellitus (GDM). We conducted a literature search for published articles on “Nutrition Therapy in reducing Gestational Diabetes” “Nutrition therapy” Gestational diabetes” “diabetes” and “Gestation” as keywords search in the Sothern Medical University Library Electronic resources (E-resources), PubMed, ScienceDirect, Web of Science and other databases including Google Scholar. A search strategy was developed for each database with no restriction on language and publication status, 75% of the papers used in this study were published in the last 5 years. Several studies have established that gestational diabetes mellitus (GDM) is an alarming health problem worldwide and is one of the most common complications of nutrition intervention in addressing GDM in pregnant women and one of the causes of the T2DM in the world. During pregnancy, it is most likely to be a critical moment for appropriate therapy and activities aimed at reducing the incidence of T2DM.